Expatriation and its effect on headquarters' attention in the multinational enterprise - Plourde, Yves; Parker, Simon C.; Schaan, Jean‐Louis (Strategic Management Journal, 2014)
We explore the circumstances under which expatriates can help their host‐subsidiary capture headquarters' attention. Our central contention is that expatriates will be particularly helpful in situations where a subsidiary or its market is showing signs of growth, allowing headquarters to recognize information signaling opportunities for the firm that could otherwise go unnoticed. We test this contention using a robust instrumental variable approach in a single multinational enterprise. Our results show that subsidiaries hosting expatriates and experiencing growth at the subsidiary or market level have a higher probability of capturing headquarters' attention . Copyright © 2013 John Wiley & Sons, Ltd.